2002
DOI: 10.4049/jimmunol.169.2.758
|View full text |Cite
|
Sign up to set email alerts
|

The B Cell Antigen Receptor Regulates the Transcriptional Activator β-Catenin Via Protein Kinase C-Mediated Inhibition of Glycogen Synthase Kinase-3

Abstract: β-Catenin is a transcriptional activator that is regulated by glycogen synthase kinase-3 (GSK-3). GSK-3 is constitutively active in unstimulated cells where it phosphorylates β-catenin, targeting β-catenin for rapid degradation. Receptor-induced inhibition of GSK-3 allows β-catenin to accumulate in the cytoplasm and then translocate to the nucleus where it promotes the transcription of genes such as c-myc and cyclin D1. Wnt hormones, the best known regulators of β-catenin, inhibit GSK-3 via the Disheveled prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
43
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(46 citation statements)
references
References 77 publications
(50 reference statements)
3
43
0
Order By: Relevance
“…Interestingly, mutations of b-catenin exon 3 were not detected in any of the analyzed samples, indicating that while deregulation of b-catenin expression is frequent, mutations in its gene are rare in cutaneous lymphomas. 23,24 When b-catenin is absent, the transcription factor TCF-1/LEF-1 acts in the nucleus as a transcriptional repressor interacting with the corepressors (TLE/Groucho and/or CtBP) of the target gene promoters. 25 Actually, it has been previously reported that b-catenin nuclear retention is mediated by the LEF-1/TCF-1 transcription factors.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, mutations of b-catenin exon 3 were not detected in any of the analyzed samples, indicating that while deregulation of b-catenin expression is frequent, mutations in its gene are rare in cutaneous lymphomas. 23,24 When b-catenin is absent, the transcription factor TCF-1/LEF-1 acts in the nucleus as a transcriptional repressor interacting with the corepressors (TLE/Groucho and/or CtBP) of the target gene promoters. 25 Actually, it has been previously reported that b-catenin nuclear retention is mediated by the LEF-1/TCF-1 transcription factors.…”
Section: Discussionmentioning
confidence: 99%
“…However, upon BCR stimulation GSK-3 is phosphorylated and GSK-3 mediated phosphorylation of ␤-catenin is inhibited. The subsequent accumulation of ␤-catenin leads to its nuclear translocation and transcriptional activity (47). Interestingly, mutations of ␤-catenin are frequently associated with NK and T cell lymphoproliferative disorders (49,50) suggesting that ␤-catenin defects may also contribute to a loss of lymphocyte homeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…Both GSK-3␣ and GSK-3␤ are expressed ubiquitously in mammalian tissues and have been shown to regulate a wide selection of cell functions including cell growth (44), cell polarity (45), and cell fate (46). In resting B lymphocytes unstimulated through their BCR, GSK-3 phosphorylates the transcriptional regulator ␤-catenin thus targeting it for degradation (47,48). However, upon BCR stimulation GSK-3 is phosphorylated and GSK-3 mediated phosphorylation of ␤-catenin is inhibited.…”
Section: Discussionmentioning
confidence: 99%
“…16 However, inhibition of GSK-3 does not inhibit the apoptotic effect of PI3K inhibitors. 7 As GSK-3 is inhibited by PKC, 37 perhaps the over-expression of active PKC-βII 38 blocks this pathway in CLL cells. We found that B cells from CLL samples were more sensitive to Akt inhibitors than T cells from CLL samples, and B or T cells from healthy donors.…”
Section: Discussionmentioning
confidence: 99%